Comparing efficiency of literature-based estimation of general biomass using Length-Weight Relationships (LWRs) between freshwater and seawater fishes - Jaehoon Yeom; Sang Don Kim (PLoS ONE, 2025)
Fish biomass estimation is crucial for understanding aquatic ecosystem dynamics and managing fisheries resources effectively. This study evaluated the applicability of estimating fish biomass in Korean aquatic ecosystems using literature-derived General Total Length (GTL) and length–weight relationships (LWRs). We compared the estimated biomasses with measured field biomasses from literatures for freshwater and seawater fish species. Data on individual biomass, habitat, and length-weight coefficients were collected from the literature and databases for 245 fish species. Biomass was estimated using the GTL and representative LWR coefficients and then they were compared to the measured field biomasses from literature. The results showed that this estimation method was applicable only to freshwater species (R² =  0.7133), whereas the estimates for seawater species showed a poor correlation (negative R² values). The removal of outliers (Q >  6) improved the estimation accuracy for the freshwater species. This study demonstrates that literature-based biomass estimation using GTL and LWRs is appropriate for freshwater fish in Korea, but not for seawater species. These findings contribute to the generation of fundamental biomass data for ecosystem modeling and highlight the need for habitat-specific approaches for biomass estimation. Since habitat specific biomass data is deficient, future research should explore biomass estimation through species extrapolation to address data gaps in aquatic ecological studies.